LA QUALITÉ DE LEADER ET SON IMPACT SUR L'EFFICACITÉ ORGANISATIONNELLE - Bouhelal Fatima; Kerbouche Mohammed (European Scientific Journal, ESJ, 2015)
This paper examines the relationship between the quality of the leader and the extent of its influence on organizational effectiveness. Through empirical research, our results revealed that the type of leadership exercised by the Directors has an important cause because it occupies an important place at the top of the pyramid of power in the organizational structure. The choice of managers is one of the important factors for the success of organizations, and leadership style can have a positive or negative impact on the organizational climate within the organization, it was found that there is some influence of the quality of leader in the effectiveness.